Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/bja/aew179
|View full text |Cite
|
Sign up to set email alerts
|

Covert stroke after non-cardiac surgery: a prospective cohort study

Abstract: NCT01369537.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 28 publications
0
35
0
1
Order By: Relevance
“…Moreover, brain magnetic resonance imaging studies suggest that 1 in 10 elderly patients has a (subclinical) covert perioperative stroke. 2 The World Health Organization considers that because of an ageing population, by 2030 chronic diseases will affect the lives of nearly 52 million inhabitants in the European region. More than 80% of people aged above 65 yr will suffer from chronic diseases, especially of the cardiovascular and neurovascular systems.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, brain magnetic resonance imaging studies suggest that 1 in 10 elderly patients has a (subclinical) covert perioperative stroke. 2 The World Health Organization considers that because of an ageing population, by 2030 chronic diseases will affect the lives of nearly 52 million inhabitants in the European region. More than 80% of people aged above 65 yr will suffer from chronic diseases, especially of the cardiovascular and neurovascular systems.…”
mentioning
confidence: 99%
“…1 From a purely practical perspective, a non-invasive metric that tracks sensory awareness and is robust to the combination of anaesthetic drugs and patient factors would be a welcome addition to the anaesthetist's perioperative tool kit. 2 From a theoretical perspective, such a metric would prove invaluable for endeavours to understand the neural basis of consciousness, and in particular, sensory awareness. 2 The contribution by Plourde and Arseneau 3 in this month's British Journal of Anaesthesia provides evidence towards that end.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a difference is furthermore not clinically relevant, but our analyses cannot exclude a larger effect of hyperoxia on cerebrovascular complications. It is furthermore likely that only a minor subgroup of patients in the PROXI trial had a primary cerebral injury or covert stroke during the exposure to study intervention, and that reduce our power to detect a potential association between perioperative hyperoxia and primary or secondary cerebral injury.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, evidence is accumulating that cerebral perfusion during general anaesthesia could be compromised more than previously thought. Magnetic resonance imaging studies have shown the incidence of covert stroke during anaesthesia may be as high as 10% in patients over 65 years of age . Since vasopressors like phenylephrine are widely used, and their exact effects on the cerebral vasculature during anaesthesia remain uncertain, we suggest that future research is needed to quantify the response of cerebral haemodynamics to commonly used anaesthetic and vasopressor drugs.…”
mentioning
confidence: 99%